PENERAPAN PERMAINAN ULAR TANGGA BERBASIS LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN DAN PEMECAHAN MASALAH DI TK NEGERI PEMBINA TAIS PADA KELOMPOK B - Apri Hayani (DIADIK, 2023)
This study aims to describe the application of an environment-based game of snakes and ladders to improve number recognition and problem solving at an early age in group B at Pembina Tais State Kindergarten. This type of research is Classroom Action Research (CAR), the research stages include 1) planning, 2) implementation, 3) observation, 4) reflection followed by quasi-experimental. The CAR subjects were children of group B1 while the quasi-experimental research sample was group B2 at Pembina Tais State Kindergarten. The data collection technique used is observation. The data obtained were then analyzed by means of the average test and t test. The tool used in data collection is an observation sheet. The observation sheets used in this study were the teacher's observation sheet and the child's observation sheet. The results of classroom action research (CAR) that have been carried out have shown an increase in the recognition of numbers in each cycle. This can be seen from the increase in every aspect of life knowing numbers. Based on the results of classroom action research (CAR) there is an increase in problem solving abilities in each cycle. This can be seen from the improvement in every aspect of problem solving life. This can be seen from the results of the t-test between cycles which show a significant difference between the first, second and third cycles